Sexualised Illness And Gendered Narratives: The Problematic Of Social Science And Humanities In China's Hiv And Aids Governance - Micollier, Evelyne (Penerbit Universiti Sains Malaysia (USM Press), 2012)
In China, the general understanding of HIV/AIDS and awareness of HIV risks has been shaped by a 1990s construction of a disease as one affecting minority groups such as drug users, gay men and prostitutes, rather than a disease contracted through high-risk behaviors, a factor that may explain a still rather low awareness of HIV risks. Gender norms and roles put both men and women at risk with regards to sexual activity even though not at the same level: while men engaging in high-risk behaviors can negotiate and exercise control of sexual activities as a way of constructing masculinity, such a process has seriously limited women's capacity to exercise control over their bodies due to their lack of power and ability to negotiate with sexual partners. This situation highlights the need for gendered empowerment and reinforces a globally assessed gendered vulnerability to HIV infection with women being most at risk. Hence, understanding the sexual transmission in the larger context of sexualised disease and gendered narratives may contribute to reframing these narratives. This calls for a social sciences and humanities approach to documenting and reframing the sexualised HIV and AIDS narratives in order to produce more adequate social and health responses and to reduce HIV and AIDS related stigma and discrimination against sexualised minorities. This article discusses the increasing prevalence of sex-related HIV and AIDS infections and cases, and hence the changing dynamic in China's HIV and AIDS epidemic. It analyses key issues related to sex and gender in China's HIV and AIDS governance. Finally it calls for a gendered and social science approach to China's HIV and AIDS governance as a way to escape the quagmire of tackling the epidemic as sexualised epidemic.